«Denglisch» as a Product of Globalized “Hybridization” of German - Mizin, Kostiantyn; Kolesnyk, Oleksandr (Studia Philologica, 2023)
This article addresses the phenomenon of Denglisch (namely English borrowings in present-day German) as a systemic "hybrid" factor in the development of the modern literary German language. Denglisch is believed to reflect the general tendency in the neology of the modern languages as well as dynamic mutations in their normative structures, impacted by globalized phenomena and processes of technological, cultural, ecological, linguistic and communicative nature. Denglisch demonstrates, on the one hand, the open character of a language system capable of modifying/updating itself. On the other hand, intensive penetration of English language signs into the German language systems causes "hybridization" of the latter. Intensive transformations observed within a relatively short period are understood as systemic mutations, mostly determined by the system’s structural and functional auto-optimization. Optimization driven by the principles of open systems’ saving energy and resources unfolds as reduction of systems’ basic surface and deep structures. Furthermore, intensive use of the optimized English verbal constructs, incorporated into the systems of various languages, German in particular, lead to the simplification of cognitive procedures and the gradual unification of linguistic cultures. Therefore, the English language may eventually turn into a planetary "common speech", while the national specific features of the German language are most likely to undergo further reduction.